DISEMINASI CIVIC EDUCATION DI MADRASAH ALIYAH NEGERI 1 SEMARANG: PERSPEKTIF SOSIOLOGI PENDIDIKAN ERA DIGITAL - Agusman; Dea Resti Jivatianto; Fatkhur Rohman; Sa’adi (STKIP Subang, 2026)
This study aims to analyze the dissemination process of Civic Education at Madrasah Aliyah Negeri 1 Semarang and to examine the strategic role of the madrasah in fostering digitally responsible citizens. The research employs a qualitative case study approach, with data collected through classroom observations, in-depth interviews with curriculum stakeholders, and document analysis. The findings reveal that the dissemination of civic values at Madrasah Aliyah Negeri 1 Semarang is implemented comprehensively through four primary channels: the integration of civic values into classroom instruction using interactive digital media; the reinforcement of school culture through flag ceremonies, national commemorative events, and religious moderation programs; student organizational activities such as the Student Council (OSIS) and the Scout Movement; and the utilization of digital platforms, including social media and the Learning Management System (LMS). Digital media play a pivotal role in strengthening students’ digital literacy by promoting critical information filtering and the creation of positive digital content. From a sociological perspective, the madrasah functions as an effective agent of socialization, transforming national values into an identity of digital citizenship characterized by intelligence, ethical awareness, and tolerance. The study demonstrates that the synergy between teachers’ exemplary conduct and technological adaptation constitutes the key factor in the successful internalization of civic values in the digital era.